Analisis Bentuk Karakter Dalam Penggunaan Media Sosial Pada Siswa SMP Kota Pontianak (Studi Kasus Di SMP Negeri Dan Swasta) - Mukhlis Novi Ardiansyah (Universitas Tanjungpura, 2020)
The purpose of this study is to Analysis Character Forms in the Use of Social Media in Pontianak City Junior High School Students (Case Study in Public and Private Junior High Schools) the character shape of students in the use of social media, is good, namely, students are able to discipline and be responsible regarding the use of social media both at school and outside school. The form of character taught to public and private junior high school students in Pontianak always be honest, disciplined, and responsible, protecting themselves from negative social media. Social media that are often used by public and private junior high school students in Pontianak, what's an app, Facebook, Instagram, and online games. The impact of the use of social media on state and private junior high school students in Pontianak City, for schools students, are given extra supervision so that social media misuse does not occur.